2021
DOI: 10.1039/d1ra00790d
|View full text |Cite
|
Sign up to set email alerts
|

Coatings of magnetic composites of iron oxide and carbon nitride for photocatalytic water purification

Abstract: Photocatalytic degradation of organic pollutants with spray coated iron oxide/CN composite films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Composites of magnetic nanoparticles randomly dispersed in a polymer matrix are promising materials widely applied in many engineering areas for magnetic separation, catalysis, MRI contrast agents, or electromagnetic shielding [1][2][3][4][5]. Polydimethylsiloxane (PDMS) is a suitable polymer for embedded composite materials that combine the properties of the matrix and the nanoparticles [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Composites of magnetic nanoparticles randomly dispersed in a polymer matrix are promising materials widely applied in many engineering areas for magnetic separation, catalysis, MRI contrast agents, or electromagnetic shielding [1][2][3][4][5]. Polydimethylsiloxane (PDMS) is a suitable polymer for embedded composite materials that combine the properties of the matrix and the nanoparticles [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained yellow powder is grinded in a mortar and sieved to a particle size smaller than 100 μm. Detailed information on synthesis and characterization of the CN photocatalyst materials was reported in reference [50]. To obtain β-Bi 2 O 3 , the [Bi 38 O 45 (OMc) 24 (EtOH) 13 ] cluster was synthesized according to reference [47] and hydrolyzed to obtain pure β-Bi 2 O 3 according to [26,51].…”
Section: Methodsmentioning
confidence: 99%
“…The as-prepared fleeces are used as substrates for the photocatalyst material. The preparation process, the characterization (SI 1; UV-vis spectra, PXRD, photoluminescence spectra, SEM) and the evaluation of the photocatalytic activity of the used CN [50] and β-Bi 2 O 3 [26,51] particles is described in the literature. To coat the fleeces with these catalyst materials, the electrospun fleeces are dipped into a solution of ethanol (EtOH) and water, which causes the polymer to swell.…”
Section: Coating Of Pvac Fleeces With Cn and β-Bi 2 Omentioning
confidence: 99%
“…A Fe 2 O 3 -TiO 2 /PVP composite layer was prepared by spray coating a mixture of the commercial oxides and polyvinylpyrrolidone on a glass pipe and tested in triclosan degra-dation under solar light in deionized water and simulated greywater effluent [139]. The authors found this immobilization procedure effective, leading to a removal up to 83%, and proposed a decomposition pathway based on the intermediates detected by LC-MS. A similar spray coating technique was used for the deposition of magnetic composites of iron oxide (α-Fe 2 O 3 and Fe 3 O 4 ) and carbon nitride (C 3 N 4 ) synthesized via a microwave-assisted hydrothermal route [140]. Such catalyst showed interesting results in the degradation of triclosan and ethinylestradiol under visible-light irradiation, particularly a TCS was degraded with up to 46% of the initial concentration within 8 h, under visible-light irradiation.…”
Section: Triclosanmentioning
confidence: 99%